2015
DOI: 10.2471/blt.14.151167
|View full text |Cite
|
Sign up to set email alerts
|

Rapid diagnostic tests for malaria

Abstract: Maintaining quality, competitiveness and innovation in global health technology is a constant challenge for manufacturers, while affordability, access and equity are challenges for governments and international agencies. In this paper we discuss these issues with reference to rapid diagnostic tests for malaria. Strategies to control and eliminate malaria depend on early and accurate diagnosis. Rapid diagnostic tests for malaria require little training and equipment and can be performed by non-specialists in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 25 publications
0
32
0
Order By: Relevance
“…The hybridization of the target oligo to only its perfectly matched complementary sequence altered the FRET‐pair distance as well as changed the physical topology of the DNA rectangle; these two processes were visualized using fluorescence microscopy and AFM, respectively. Plasmodium falciparum lactate dehydrogenase (PfLDH), a parasite secreted biomarker that is found in elevated amounts in malaria patients, is a key target biomarker for field‐deployable rapid diagnostic tests . PfLDH sensing was similarly demonstrated by capturing the molecule using PfLDH‐specific aptamers on another DNA rectangle and again characterized by AFM .…”
Section: Dna Nanostructures As Biomedical Sensorsmentioning
confidence: 99%
“…The hybridization of the target oligo to only its perfectly matched complementary sequence altered the FRET‐pair distance as well as changed the physical topology of the DNA rectangle; these two processes were visualized using fluorescence microscopy and AFM, respectively. Plasmodium falciparum lactate dehydrogenase (PfLDH), a parasite secreted biomarker that is found in elevated amounts in malaria patients, is a key target biomarker for field‐deployable rapid diagnostic tests . PfLDH sensing was similarly demonstrated by capturing the molecule using PfLDH‐specific aptamers on another DNA rectangle and again characterized by AFM .…”
Section: Dna Nanostructures As Biomedical Sensorsmentioning
confidence: 99%
“…Populations living in remote areas were frequently neglected. Today RDTs overcome many bottlenecks encountered by microscopy: it is faster to train unskilled personnel to use RDTs than to train a good microscopy technician; there is no ‘fatigue’ or loss of blood smear reading skills because of a rarity of positive cases in a context of decreasing incidence; and, RDTs are easy to supply [ 22 , 23 ]. Recent systematic reviews have concluded that RDT interpretation and performance are satisfactory when handled by trained community members and can result in the appropriate prescription of ACT for confirmed P. falciparum cases [ 24 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent improvements in RDT sensitivity and specificity mean that they perform as well as microscopy for symptomatic falciparum malaria infections in many settings [ 27 ]. RDTs can reliably discriminate between P. falciparum and P. vivax infections [ 22 , 28 , 29 ]. The good performances achieved by RDTs should be taken as strong encouragement to further develop this tool.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular biology, however, remains expensive for many countries in endemic areas [16]. Serologic assays constitute a good alternative for epidemiological survey and blood donor screening, given that, antibodies reflect exposure to pathogens [17].…”
Section: Introductionmentioning
confidence: 99%